Expression of Concern: Functional Improvement of Regulatory T Cells from Rheumatoid Arthritis Subjects Induced by Capsular Polysaccharide Glucuronoxylomannogalactan (PloS one, 2021)
The corresponding author has stated that there were errors in selection of western blot images for Figs 1 and 6 as follows: - In the originally published Fig 1A, the panels for Control cells are not taken from the same replicate experiment as the panels for the RA cells. Culture supernatants were collected after 2, 18 and 72 h to test TGF-β1 and IL-10 levels by specific ELISA assays. *, p<0.05 (triplicate samples of 7 different Control and RA; RA GXMGal-treated vs untreated cells); †, p<0.05 (triplicate samples of 7 different Control and RA; RA MTX-treated vs untreated cells) (C). https://doi.org/10.1371/journal.pone.0247971.g001 - In the originally published Fig 6A, the panels for Control cells are not taken from the same replicate experiment as the panels for the RA cells. (2014) Functional Improvement of Regulatory T Cells from Rheumatoid Arthritis Subjects Induced by Capsular Polysaccharide Glucuronoxylomannogalactan.